Forage sorghum lines submitted to water deficit stress under controlled conditions - Amaral, Sérgio Ribeiro do; Lira, Mário de Andrade; Tabosa, José Nildo; Santos, Mércia Virginia Ferreira dos; Mello, Alexandre Carneiro Leão de; Santos, Venésio Felipe dos (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effects of water deficit stress on establishment, development and survival rate of 11 forage sorghum lines in a greenhouse. The experiment was carried out under a randomized block design, with split-splot arrangement and five replications. Each replication was formed by a container of 250 L capacity, filled with 187.9 kg of sandy soil. Two stress periods were studied, with three irrigations, at the begining of tests and when the plants showed large numbers of dry leaves. During the first period all lines had high survival rates showing resistance to water deficit stress. Slower growing lines suffered less with the imposed water deficit. During the second water deficit stress period there were no significant differences between the lines in plant development. Along both stress periods, growth rate did not distinguish satisfactorily lines with distinct behavior, as relate to drought resistance, when those lines were competing on the same recipient and high population density. Lines 84, 29, 99, 41, 63, and 104 had higher stress resistant while lines 33, 38, 40, 67, and 92 had lower stress resistant.